Agricultural Modernization and Rural Development: A Case Study of Mahamaya Nagar District, Uttar Pradesh - Ahmad, Mumtaj; Islam, Pasarul (National Geographical Journal of India, 2022)
In the present paper an attempt has been made to examine the impact of agricultural modernization on rural development in Mahamaya Nagar district, Uttar Pradesh. The study is based on secondary sources of data obtained from District Census Hand Book (2011) and Sankhyikiya Patrika (SP) published by Economics and Statistical Division (ESD), Government of Uttar Pradesh (2014). Block has been taken as unit of study. The level of agricultural modernization is determined with the help of sixteen indicators while eighteen indicators for rural development. Z-score technique has been applied to calcu- late the levels of Agricultural Modernization and Rural development and finally agricul- tural modernization vis-a-vis rural development map has been prepared through standard deviation formula of high, medium and low. The study reveals that there are integrated as well as reverse relationships between agricultural modernization and rural development in the district.